Quantitative and Orthogonal Formation and Reactivity of SuFEx Platforms. Issue 41 (27th June 2018) - Gahtory, Digvijay; Sen, Rickdeb; Pujari, Sidharam; Li, Suhua; Zheng, Qinheng; Moses, John E.; Sharpless, K. Barry; Zuilhof, Han
Abstract: The constraints of minute reactant amounts and the impossibility to remove any undesired surface‐bound products during monolayer functionalization of a surface necessitate the selection of efficient, modular and orthogonal reactions that lead to quantitative conversions. Herein, we explore the character of sulfur–fluoride exchange (SuFEx) reactions on a surface, and explore the applicability for quantitative and orthogonal surface functionalization. To this end, we demonstrate the use of ethenesulfonyl fluoride (ESF) as an efficient SuFEx linker for creating "SuFEx‐able" monolayer surfaces, enabling three distinct approaches to utilize SuFEx chemistry on a surface. The first approach relies on a di‐SuFEx loading allowing dual functionalization with a nucleophile, while the two latter approaches focus on dual (CuAAC–SuFEx/SPOCQ–SuFEx) click platforms. The resultant strategies allow facile attachment of two different substrates sequentially on the same platform. Along the way we also demonstrate the Michael addition of ethenesulfonyl fluoride to be a quantitative surface‐bound reaction, indicating significant promise in materials science for this reaction. Abstract : The sulfur–fluoride exchange (SuFEx) reaction provides a fast and quantitative handle to functionalize a wide range of platforms. Here we show both the versatility and orthogonality of the SuFEx reaction with amine nucleophiles, and the easy accessibility of SuFEx‐able platforms by the quantitative reaction of ethene sulfonyl fluoride with surface‐bound amines.